(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
This paper describes the details of the aeroradiometric operations, the radiation detection system used and discusses the results. The low-altitude survey was carried out over Goiânia a few days after information of the accident was received by the national competent authority, the Brazilian Nuclear Energy Commission (CNEN). Given the little information at the time of the accident and the urgency to respond to the local and federal authorities, an aerial radiometric survey was proposed to evaluate the extent of the contamination and dispersion of the radioactive powder. The city’s entire urban area and nearby dwellings centers, plus the two creeks crossing the city were surveyed in two days. The survey found only one additional contamination point 2.8 x 10-4 C/kg/h (1.1 R/h) that had not yet been identified by ground survey crews. Furthermore, no contamination was found along the margins of the Capim Puba Creek and Meia Ponte rivers which could be contaminated due to rainwater common at that time of the year. Detection tests conducted at different altitudes over the main contamination area showed that the Cs-137 gamma radiation could be detected even at altitudes of 350m above the ground. This was much higher than the 40 m - 70 m decided for the overflights. The survey demonstrated that the contamination was restricted to a few locations in the neighborhood of the metal scrap place where the source shield was broken. These locations were under the control of CNEN radiological emergency response personnel. Such a finding was an important indicator to calm down the population and the government authorities. This allowed concentrating attention on the remediation of the known points of high gamma activity.